Inflammatory bowel diseases during the COVID-19 pandemic - Edyta Derda; Edyta Szymańska; Magda Sokolek; Jarosław Kierkuś (Gastroenterology Review)
Since the beginning of the COVID-19 pandemic in 2020, the safety of those with compromised immune systems and chronic disease has been of particular concern for health care providers. Inflammatory bowel diseases (IBD) are chronic, incurable conditions of digestive system with unknown aetiology, but one of the causes is disordered immune response. Medical therapies most frequently used in IBD are immune suppressing or modifying with the rising use of biologic treatment. All these aspects make patients with Crohn’s disease and ulcerative colitis a group of particular risk. Therefore, the aim of this review is to discuss potential mechanisms, risks, and management of patients with IBD during COVID-19 pandemic.